A investigação da geografia fílmica a partir do ordenamento tópico no cinema - Sobral, Katia Antunes (2016)
This search is a geographical investigation of the movies from its location of filmic elements in place. Thus, the location in the movie is examined from the geographicity called the filmic Geography. This is the localization planning in movie from the filmic place (picture) built by the shooting techniques, such as: lighting, color, framing and camera speed, and the assembly, related to the distribution , the order of scale and the distance of the elements each other and the viewer. In order to illustrate these assumptions filmic Geography and its importance for the geographic analysis of the world examined the following filmographies: The Searchers (USA, 1956, 120 minutes Direction: John Ford), The Given Word (O Pagador de Promessas, Brazil, 1962, 97 minutes Director:. Anselmo Duarte), Rear Window (USA, 1954, 114 minutes Direction:. Alfred Hitchcock), Strike (Statchka, USSR, 1924, 82 minutes Director:. Sergei Eisenstein) and Black God, White Devil (Deus e o Diabo na Terra do Sol, Brazil, 1964, 110 minutes Direction:. Glauber Rocha)